Genome-wide CRISPR/Cas9 screening identifies host factors critical for antiviral defense against equine herpesvirus type 1 - Li, Ziqian; Yu, Tingting; Ge, Lijuan; Lv, Shubing; Fu, Qiang; Shi, Huijun (Frontiers in Immunology, 2026)
IntroductionEquine herpesvirus type 1 (EHV-1) is a major veterinary pathogen causing significant economic losses in the livestock industry. Despite its impact, effective vaccines and targeted antiviral strategies remain limited, largely due to an incomplete understanding of host factors regulating viral replication and pathogenesis.MethodsTo systematically identify host genes essential for EHV-1 infection, we established a BHK-21 cell line stably expressing Cas9 and performed a genome-wide CRISPR/Cas9 knockout screen using a pooled lentiviral single-guide RNA library. Significantly enriched candidate genes from positive selection were validated by generating knockout cell lines. Viral replication and protein expression were assessed using quantitative polymerase chain reaction and Western blot analysis. Pathway enrichment and protein interaction network analyses were subsequently conducted.ResultsGenome-wide CRISPR/Cas9 screening identified multiple host factors critical for EHV-1 replication. Pathway enrichment analysis revealed that these genes were involved in key cellular signaling and regulatory networks associated with viral infection. Functional validation demonstrated that knockout of selected host genes significantly suppressed EHV-1 replication and viral protein synthesis.DiscussionThese findings highlight essential host determinants required for EHV-1 replication and suggest that targeting host factors may represent a promising strategy for antiviral intervention. This study provides a foundation for the development of host-directed immunotherapeutic and antiviral approaches against EHV-1 infection.